2023
DOI: 10.1002/jmv.29318
|View full text |Cite
|
Sign up to set email alerts
|

Azvudine and nirmatrelvir–ritonavir in hospitalized patients with moderate‐to‐severe COVID‐19: Emulation of a randomized target trial

Yiling Zhou,
Yi Liu,
Li Jiang
et al.

Abstract: To examine the effectiveness of azvudine and nirmatrelvir–ritonavir in treating hospitalized patients with moderate‐to‐severe COVID‐19. We emulated a target trial with a multicenter retrospective cohort of hospitalized adults with moderate‐to‐severe COVID‐19 without contraindications for azvudine or nirmatrelvir–ritonavir between December 01, 2022 and January 19, 2023 (during the Omicron BA.5.2 variant wave). Exposures included treatment with azvudine or nirmatrelvir–ritonavir for 5 days versus no antiviral tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…In a multicenter retrospective randomized cohort study, azvudine demonstrated a signi cant reduction in overall mortality rates and a decrease in the need for tracheal intubation in moderate to severe patients with COVID-19. [14] In a cohort study comparing Nirmatrevir-Ritonavir and azvudine, the latter showed comparable e cacy in slowing disease progression and reducing all-cause mortality rates in hospitalized patients with COVID-19. [10] Although the results of the Phase III clinical trials have not been formally published, several studies have indicated that azvudine can signi cantly reduce the proportion of disease deterioration and effectively lower the overall mortality rates in real-world applications.…”
Section: Discussionmentioning
confidence: 98%
“…In a multicenter retrospective randomized cohort study, azvudine demonstrated a signi cant reduction in overall mortality rates and a decrease in the need for tracheal intubation in moderate to severe patients with COVID-19. [14] In a cohort study comparing Nirmatrevir-Ritonavir and azvudine, the latter showed comparable e cacy in slowing disease progression and reducing all-cause mortality rates in hospitalized patients with COVID-19. [10] Although the results of the Phase III clinical trials have not been formally published, several studies have indicated that azvudine can signi cantly reduce the proportion of disease deterioration and effectively lower the overall mortality rates in real-world applications.…”
Section: Discussionmentioning
confidence: 98%